1986
DOI: 10.1111/j.1745-4557.1986.tb00853.x
|View full text |Cite
|
Sign up to set email alerts
|

LIPIDS IN SUBCUTANEOUS TISSUES AND LONGISSIMUS MUSCLES OF FEEDLOT AND GRASS‐FED EWES1

Abstract: Subcutaneous and intramuscular lipids from feedlot-and grass-fed ewes were studied to determine if diet would influence fatty acid composition of these older animals. Subcutaneous lipid of ewes from the feedlot-fed group contained more 4-methyl branched acids, less is0 and anteiso branched acids, less stearic acid and more octadecenoic acid than grassfed ewes. Only small amounts of medium chain acids (10-15 carbons) were noted in longissimus muscle lipids from both dietary groups and essentially all of them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
4

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 16 publications
2
7
0
4
Order By: Relevance
“…For pasture feeding, lower concentrations of 4-Me-8:0 and 4-Me-9:0 were reported compared to concentrate feeding (Priolo et al, 2001;Young et al, 2003). Similar results were reported for other BCFAs, such as 4-Me-10:0, 4-Me-12:0 and 4-Me-14:0 (Miller et al, 1986), even though only low amounts of BCFA could be found in plants (Diedrich and Henschel, 1990). BCFAs are formed mainly from microbial metabolism in the rumen (Chilliard et al, 2003).…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…For pasture feeding, lower concentrations of 4-Me-8:0 and 4-Me-9:0 were reported compared to concentrate feeding (Priolo et al, 2001;Young et al, 2003). Similar results were reported for other BCFAs, such as 4-Me-10:0, 4-Me-12:0 and 4-Me-14:0 (Miller et al, 1986), even though only low amounts of BCFA could be found in plants (Diedrich and Henschel, 1990). BCFAs are formed mainly from microbial metabolism in the rumen (Chilliard et al, 2003).…”
Section: Introductionsupporting
confidence: 75%
“…Brennand and Lindsay (1992) reported higher concentrations of 4-Me-8:0, 4-Et-8:0 and 4-Me-9:0 in FAT than in MEAT, which supports the results of the present study. Miller et al (1986) reported lower levels K. F. Schiller et al: Concentrations of branched chain fatty acids in lambs of other BCFAs (4-Me-10:0, 4-Me-12:0 and 4-Me-14:0) in MEAT than in FAT, partly below the limit of quantification. For all three BCFAs, significant differences between specific crosses were detected.…”
Section: Discussionmentioning
confidence: 99%
“…A ausência de ácidos carboxílicos nos extratos caprinos foi justificada pelo baixo teor de gordura da carne caprina, cujo teor variou de 1,62 a 5,42% [11,13,14]. MILLER, FIELD & AGBOOLA [15] reportaram que os ácidos graxos de cadeira ramificada ocorrem em maiores concentrações na gordura subcutânea quando comparada com a gordura muscular de ovinos.…”
Section: -Resultados E Discussãounclassified
“…Os coeficientes de determinação indicaram que houve um ajustamento eficiente dos dados em torno da curva, com exceção de alguns casos apontados na tabela. [23], SOLOMON et al [36], LOUGH et al [21] e por TICHENOR et al [38], com variação entre 1,74 a 3,29%.…”
Section: -áCidos Graxos Saturadosunclassified
“…Os coeficientes de determinação (R2) mostram que houve ajustamento eficiente dos dados em torno da curva. [23] e SOLOMON et al [36], cuja variação foi de 1,59 a 2,51%. Comparando o efeito das raças sobre as percentagens do ácido oléico (C18:1ω9) em função do peso de abate, que ajustaram-se em curvas lineares positivas, observa-se que a raça Bergamácia apresentou valores de C18:1ω9 menores que a raça Santa Inês, mas essa diferença estreitou-se com o aumento do peso ao abate.…”
Section: -áCidos Graxos Monoinsaturadosunclassified